Les transitions professionnelles des personnes de type conventionnel - Riverin-Simard, Danielle; Delmotte, Claudine (Canadian Journal of Counselling and Psychotherapy, 2007)
This article explores the vocational development of the conventional types and its link with the socio-professional transitions forced on them, among other variables, by the present socioeconomical conditions. The study of a sample of 190 subjects contributes to a better knowing of the complex aspects of P-E interaction and corroborates the necessity to take them into account, given the importance these individuals attach to their organizational environment. The conclusion puts forward some practical implementations.